Potential value of serum brain-derived neurotrophic factor, vascular endothelial growth factor, and S100B for identifying major depressive disorder in knee osteoarthritis patients - Zhang, Peng; Xiong, Yuyuan; Wang, Bangjun; Zhou, Yi; Wang, Zijian; Shi, Jiaqi; Li, Chao; Lu, Xinyan; Chen, Gang (Frontiers in Psychiatry, 2022)
Background The chronic pain and functional limitations in osteoarthritis (OA) patients can increase risk of psychiatric disorders, e.g., major depression disorder (MDD), which may further aggravate the clinical symptoms of OA. Early detection of MDD is essential in the clinical practice of OA. Materials and methods Two hundred and fifteen participants with knee OA were recruited, including 134 MDD patients (i.e., MDD group) and 81 ones without MDD (i.e., control group). Among them, 81 OA participants in the control group received a 3-year follow-up and were divided into trans-MDD group (who transforming into MDD; N = 39) and non-MDD group (who keeping non-MDD; N = 42) at the end of the follow-up. The 17-item Hamilton Depression Scale (HAMD-17), Self-Rating Depression Scale (SDS), and Visual Analogue Scale (VAS) were performed. Furthermore, serum levels of brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF), S100B, and IGF-1 were detected. Results (1) Compared with OA participants without MDD, there were significant decrease in serum BDNF and significant increase in serum VEGF and S100B and VAS scores in OA participants with MDD. (2) A mediation of the association was found between the VAS scores and the HAMD-17 scores through the BDNF as mediator in OA participants with MDD. (3) Significantly lower baseline BDNF levels and higher baseline S100B levels were detected in OA participants who transforming to MDD after a 3-year follow-up when compared with those who keeping non-MDD. (4) In the trans-MDD group, significant associations of the change of serum BDNF levels with rate of change of HAMD-17 scores were found, and baseline serum S100B levels positively correlated with the HAMD-17 scores at the end of the follow-up. (5) In OA participants, the composite indicator of BDNF, VEGF, and S100B differentiated MDD patients from controls with the area under the curve (AUC) value of 0.806, and the combined indicator of baseline BDNF and S100B distinguished trans-MDD participants from non-MDD ones with an AUC value of 0.806. Conclusion Serum BDNF, VEGF, and S100B may be potential biomarkers to identify MDD in OA patients. Meanwhile, serum BDNF and S100B shows great potential to predict the risk of MDD for OA.